Interactive e-modules training and workshop as teaching materials the era of Society 5.0 - Kusumawati Dwiningsih; Sri Poedjiastoeti; Ahmad Lutfi; Sukarmin Sukarmin; Rusly Hidayah; Ainun Nisa (University of Merdeka Malang, 2022)
Interactive e-modules are one of the innovations of teaching materials in Society 5.0 considered innovative for learning. As innovative teaching materials interactive e-modules are recommended, it is hoped that 21st-century teachers will be able to develop their interactive e-modules that suit students’ character and the learning methods used. However, based on a survey that has been conducted, 79% of teachers still use PowerPoint (.ppt) as teaching materials. This activity was held to provide training on making interactive e-modules to the chemistry MGMP team in Gresik based on a scientific approach. This interactive e-module is equipped with teaching materials such as pictures, videos/animations, quizzes, and interactive features to attract students’ attention. The methods used in this service include coordination, interactive e-module design, instrument creation, training implementation, evaluation, management, and publication. Analysis of data obtained from training activities proves that teachers are interested in creating and using interactive e-modules for learning. The interactive e-module is considered an attractive design for learning following the era of Society 5.0.